How do you solve x^2/(x^2-4) = x/(x+2)-2/(2-x)?

1 Answer
Mar 24, 2018

There is no solution

Explanation:

x^2/(x^2-4)=x/(x+2)-2/(2-x)
Becomes x^2/(x^2-4)=x/(x+2)+2/(x-2)

On the right side, multiply and divide first fraction with x-2
On the right side, multiply and divide second fraction with x+2
We get,

Becomes x^2/(x^2-4)=(x(x-2))/((x+2)(x-2))+(2(x+2))/((x-2)(x+2))

Becomes x^2/(x^2-4)=(x^2-2x + 2x + 4)/(x^2-4)

Becomes x^2/(x^2-4)=(x^2 + 4)/(x^2-4)

Becomes x^2=(x^2 + 4)

There is no solution